Особливості функціонування вищої школи України в умовах формування громадянського суспільства - Костючков, С. К. (НТУ "ХПІ", 2015)
У статті розглянуто особливості функціонування вищої школи України в умовах нового громадянського суспільства; підкреслюється, що в першій декаді ХХІ століття в Україні відбуваються кардинальні, навіть доленосні соціально-політичні, економічні, культурні й духовні трансформації, а саме: розвиваються механізми ринкової економіки, функціонують інститути демократії та багатопартійна система, українське суспільство стало більш монолітним, патріотично орієнтованим, відкритим. Автор акцентує увагу на тому, що на відміну від традиційних практик, формування громадянського суспільства в Україні відбувається як під тиском глобальних змін, так і у межах процесу модернізації, тобто комплексу соціальних, економічних, політичних, культурних та інтелектуальних трансформацій, характерних для країн молодих демократій. Зазначено, що громадянське суспільство хоча і є у певному розумінні поняттям трансісторичним, у кожну епоху когерує із проявами політичного життя і реагує на його стимули, а отже – приймаючи на себе знакозмінні навантаження, забезпечує соціальну раціональність, виявляючи себе як постійно змінюване, а отже – безперервно нове громадянське суспільство.

In the article the peculiarities of Higher Education of Ukraine in the new civil society; stresses that in the first decade of the XXI century in Ukraine there are drastic, even vital socio-political, economic, cultural and spiritual transformation, namely developing mechanisms of market economy, democratic institutions and functioning multiparty system, Ukrainian society has become more monolithic, patriotically oriented, open. Based on the fact that our country is in the process of civil society and the state and the society are aware of the need to ensure the implementation of established productive in some way the historical function of civil society, including: representation and protection of interests of social groups, production and delivery of social services creating conditions for the formation of the so-called middle class, public control over the actions of the authorities, finding and implementing mechanisms to address the urgent humanitarian problems of society, including - the problems of the educational sector. The author emphasizes that unlike traditional practices of civil society in Ukraine is under pressure as global change and modernization within the process that is complex social, economic, political, cultural and intellectual transformations, typical for countries emerging democracies. The current stage of social development requires a certain revision usual forms of social life, which disappeared a sense of "we", focused on achieving justice and solidarity. Only a small social formations modern man is what makes it "great" community only within small social group feels it has the understanding and compassion, solidarity, hope gets justice, because all these social characteristics are not abstract, but certainly specific, which leads to the domination of the moral foundations of social life. It is noted that although civil society is in one sense the notion transhistorical in every age agrees manifestations of political life and responds to its stimulus, and therefore – taking the opposite loads, provides social rationality, manifesting itself as continuously changing, so – continuously new civil society.
Features of high school of Ukraine under the formation of civil society
Keywords: система освіти; особистість; держава; модернізація; транзит демократичний; civil society; individual; education system; state; modernization; democratic transit